Ecclesiology of the Migrant Worker Diaspora: Communion, Migration, and Transnational Pastoral Practice - Sibagariang, Monalisa (Cattleya Darmaya Fortuna, 2024)
The phenomenon of the Indonesian migrant worker diaspora has posed a theological and pastoral challenge for the contemporary church. Human mobility across borders not only creates social and economic change but also shakes the traditional understanding of the church as a community bound by space and institutions. In this context, diaspora ecclesiology offers a reflective framework for understanding the church's presence amidst the migration and separation of its people. The church is called to reinterpret its identity as the universal, dynamic body of Christ, transcending geographical and cultural boundaries. The Eucharist, or Holy Communion, is a central symbol in shaping diasporic spirituality. Amid isolation and longing for home, communion offers an experience of communion that transcends physical distance. Through communion, migrants rediscover their identity as part of the one body of Christ, despite being scattered across various countries and under diverse working conditions. The Eucharist becomes a concrete manifestation of God's presence in the experience of human mobility and a reminder that God accompanies His people throughout their journey. In this pastoral reality, ministry to diaspora communities demands a new, transnational model. The church can no longer focus solely on those who remain, but also on those who are mobile and on the move. Transnational pastoral practice presupposes interchurch networks, the use of digital media, and ecumenical collaboration to reach people in destination countries. Online services, virtual masses, and online prayer communities are new forms of communion that reflect the face of both the digital and diaspora church. This approach also contains social and ethical dimensions. The church is not only called to serve spiritually but also to fight for justice for migrant workers who often experience exploitation and structural injustice. In this regard, the theology of migration becomes a theology of liberation that sides with those who are excluded and marginalized. A church that lives in solidarity with migrants displays the face of Christ present among the little people, who seek refuge and hope in a foreign land. This research methodology uses a qualitative-theological approach with literature study and contextual reflection. Various academic literature, church documents, and the empirical experiences of diaspora communities serve as data sources for reinterpreting the concept of the church in the context of globalization and migration. The analysis is conducted through theological hermeneutics to discover the spiritual and ecclesiological meaning of communion, migration, and transnational pastoral practice. This research is expected to contribute to the development of contextual ecclesiology in Indonesia, particularly in facing the dynamics of globalization and cross-border movements of people.The Church is expected to be an open, inclusive, and adaptive space to changing times, without losing the essence of its calling as the one body of Christ. Thus, the ecclesiology of the migrant worker diaspora reflects faith in God who continues to accompany His people on every journey, both at home and abroad.